DUSTINESS OF URBAN AREAS DURING EARTHWORKS AND CONSTRUCTION AND FINISHING WORKS - Alexandra Borisovna Strelyeva; Ekaterina Alekseevna Kalyuzhina (Современная наука и инновации, 2022)
The complex of construction works very much influences the ecology of urban environments, as well as the health. Various types of construction work are characterized with a large amount of dust formation. Particularly melodispersed dust adversely affects human health. Thereby causing numerous diseases. One of the main reguirements that are set for construction is to ensure environmental safety